Kajian Teori Humanistik Maslow dalam Kurikulum 2013 - Yunailis, Murida (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2019)
The 1945 Constitution mandates that education is the right of all Nations. Every citizen has the right to education which guides him to a better life and adapts. For this reason, an effective curriculum is needed to develop students' interests and talents. Indonesia has experienced a number of curriculum changes since independence until now which have embraced the 2013 curriculum. In general, the 2013 curriculum has characteristics and is in harmony with Maslow's Humanistic theory. If all parties work together in implementing the 2013 curriculum it will produce actualized students.